2014
DOI: 10.1016/j.neuint.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transcribed ultraconserved regions of genome in rat cerebral cortex

Abstract: Emerging evidence indicates that 481 regions of the genome (>200 bp) that actively transcribe noncoding RNAs shows 100% homology between humans, rats and mice. These transcribed ultraconserved regions (T-UCRs) are thought to control the essential regulatory functions basic for life in rodents and mammals. Using microarray analysis, we presently show that 107 T-UCRs are actively expressed in adult rat cerebral cortex. They are grouped into intragenic (61) and intergenic (46) based on their genic location. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…By combining large-scale genome-wide expression analysis and in situ hybridization detection, several groups showed that T-UCEs are differentially expressed in both time and space with highly restricted expression in selected regions of the mammalian embryo [ 117 119 ]. High-resolution screening of RNA sequence signals derived from annotated ultraconserved sequences revealed that 76 UCEs are actively transcribed and specifically enriched in the nervous system of developing brain at embryonic day E14.5 [ 119 ]. In particular, T-UC.77, T-UC.338, T-UC.377, and T-UC.359 show dynamic expression profiles increasing during E12.5–E18.5 of mouse brain development.…”
Section: Transcribed Ucesmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining large-scale genome-wide expression analysis and in situ hybridization detection, several groups showed that T-UCEs are differentially expressed in both time and space with highly restricted expression in selected regions of the mammalian embryo [ 117 119 ]. High-resolution screening of RNA sequence signals derived from annotated ultraconserved sequences revealed that 76 UCEs are actively transcribed and specifically enriched in the nervous system of developing brain at embryonic day E14.5 [ 119 ]. In particular, T-UC.77, T-UC.338, T-UC.377, and T-UC.359 show dynamic expression profiles increasing during E12.5–E18.5 of mouse brain development.…”
Section: Transcribed Ucesmentioning
confidence: 99%
“…3 , top panel). Of note, some T-UCEs remain expressed in adult brain, functioning in homeostasis in the cerebral cortex [ 119 ].
Fig.
…”
Section: Transcribed Ucesmentioning
confidence: 99%
“…3 Total RNA was extracted from peri-infarct cortex at 3h, 6h and 12h of reperfusion and hybridized to Arraystar lncRNA microarrays (n=3/group). 2 Expression data were analyzed with GeneSpring GX V11.0 software. Post-ischemic changes in the expression of T-UCRs and their host gene mRNAs were validated by real-time PCR (n=4/group).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic coordinates and the exon, intron and exon-intron overlap of T-UCRs were determined by bioinformatics. 2 Molecular functions and biological process networks of up/downstream and host genes of T-UCRS was determined with PANTHER algorithm. 2…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation